Maternal anti‐HBVs suppress the immune response of infants to hepatitis B vaccine. Issue 12 (29th July 2016) - Chen, X.; Gui, X.; Zhang, L.; Huang, F.; Zhong, H.; Pang, Z.; Wang, S.; Tang, L.; Fu, L.; Peng, Y.; Shellman, Y.
Summary: It is still controversial whether maternal anti‐HBV antibodies (anti‐HBVs) affect the infants' immune response to hepatitis B virus (HBV) vaccination. This multicentre study aims to address this question. First, we determined whether the transplacental transfer of maternal anti‐HBVs occurs by measuring the titres of 90 anti‐HBVs‐positive pregnant women and their newborns. The anti‐HBVs‐positive rates of newborns ranged from 89.7% to 100.0%, depending on the maternal anti‐HBVs titres. Secondly, we investigated the effects of maternal anti‐HBVs on the immune response of infants to HBV vaccination. A total of 1063 mother‐and‐infant pairs were enrolled and divided into three groups with maternal anti‐HBVs titres of <10 IU/L (negative – 37.9%), 10–499 and ≥500 IU/L. The infants' anti‐HBVs‐positive rate and titres were negatively correlated with maternal anti‐HBVs titres: the anti‐HBVs‐positive rate of infants were 88.9% (360/405), 84.5% (381/451) and 77.3% (160/207) in mothers with low, intermediate and high antibody titres, respectively, P <.0001. Median titres of anti‐HBVs (IU/L) among infants were 169.1, 141.0 and 79.4, respectively, P =.020. One hundred and sixty‐two infants were negative for anti‐HBVs after the standard vaccination, and 120 of 131 of these infants (91.6%) reached anti‐HBVs positivity after the first "booster" dose. The maternal anti‐HBVs titres did not significantly affect infant response to this booster. In summary, transplacental transfer of anti‐HBVs occurs and high titres of maternal anti‐HBVs may suppress the immune response of infants to the standard HBV vaccination. The current schedule of the 0, 1 and 6 month may not be the optimal choice of infants with anti‐HBVs‐positive mothers.